2000
DOI: 10.2113/gseegeosci.6.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific variation in the potentiometric response to subsidence above active longwall mining

Abstract: Longwall underground coal mining produces major changes in the hydraulic properties and groundwater levels of overlying shallow aquifers because of the fracturing associated with mine subsidence. Many aspects of these impacts remain unclear and unpredictable, particularly the variations in response between different sites. Our detailed, long-term studies of subsidence strains and hydraulic responses at sites in Illinois address this and other aspects of the conceptual model. At a study site in Saline County, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Results of the hydrological studies at the Saline County site have been reported by Booth et al (1994Booth et al ( , 1997Booth et al ( , 2000 and of the geochemical studies by Booth & Bertsch (1999). Kelleher et al (1991), Van Roosendaal et al (1990, 1994 and Trent et al (1996).…”
Section: Saline County Sitementioning
confidence: 65%
See 1 more Smart Citation
“…Results of the hydrological studies at the Saline County site have been reported by Booth et al (1994Booth et al ( , 1997Booth et al ( , 2000 and of the geochemical studies by Booth & Bertsch (1999). Kelleher et al (1991), Van Roosendaal et al (1990, 1994 and Trent et al (1996).…”
Section: Saline County Sitementioning
confidence: 65%
“…Summarizing the above, the following composite model (expressed in Fig. 3) is adapted from Booth et al (2000). The figure shows, from the bottom up, the longwall mine, the caved and heavily fractured zones, the major confining layer and a fractured shallow aquifer overlain by a shallow confining layer.…”
Section: Recovery Of Water Levels After Miningmentioning
confidence: 99%
“…Xing et al and Xu et al classified key strata structures in shallow coal seams and analyzed their structural stability [8,9]. Related scholars used field tests, theoretical analysis, and numerical simulations to study overlying strata movement, mining subsidence, surface mining-induced fissures, and so on, providing principle for supporting design, subsidence trough reclamation, and ecological restoration in the mining area of shallow coal seam [10][11][12][13][14]. Zhang et al, Booth and Bertsch, and Ma et al carried out researches on mininginduced fissures of overlying strata from the perspectives of the structure characteristics of key strata and water-resisting key strata, providing water-preserved mining technologies in shallow buried coal seam [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although many effects of LMS, for example effects on the built environment (Bell et al 2000(Bell et al , 2005Bell and Genske 2001;Bullock and Bell 1997;McNally 2000;Singh 1992), changing ground water (Booth 2006;Booth and Bertsch 1999;Booth et al 1998Booth et al , 2000Karaman et al 1999Karaman et al , 2001Zipper et al 1997), and surface water hydrology (Bell and Genske 2001;Bell et al 2000;Sidle et al 2000), are generally well understood, the potential effects of LMS on agricultural productivity are not as well understood.…”
Section: Introductionmentioning
confidence: 99%